ANALISIS LOGAM ZINK (Zn) DAN BESI (Fe) AIR SUMUR DI KELURAHAN PANTOLOAN KECAMATAN PALU UTARA - Rahayu, Budi; Napitupulu, Mery; Tahril, Tahril (Jurnal Akademika Kimia, 2013)
A study is carried out to determine the metal content of zinc (Zn) and iron (Fe) in well water samples by AAS using a wet method of destruction through the addition of concentrated HNO3 as a solvent and forming acidic. The measuring the levels of zinc in the sample performed at a wavelength (Î») = 213 nm and measuring the levels of iron in the sample performed at a wavelength (Î») = 248.3 nm. The results obtained for the levels of zinc metal respectively are 0.3121 mg/L, 0.1175 mg/L, and 0.0478 mg/L, and iron metal levels are 0.394 mg/L, 0.546 mg/L, and 0.324 mg/L. These data indicate the metal content of zinc in wells water Pantoloan Village North Palu Palu district is still below the threshold value while the metal content of iron in wells near the sea (sampel B) is above the standard threshold value defined in the Rules of Ministry of Health Decree No. 492 /2010.